Comparative Additional Factor for Diffraction Loss On (TEM01) Mode from That of (TEM00) Mode - Twana Mohammed Kak Anwer; Suran Dunun Yaseen (Zanco Journal of Pure and Applied Sciences, 2022)
In this paper, the tendency is towards looking for a correction factor in the diffraction loss from (TEM01) in order to search for the same parameters, diffraction loss in a cavity has standing (TEM01) modes. This will be through a lengthy analysis in the far-field intensities the waves via – Gaussian beam shaped wave patterns. The analysis is in the same criteria as that of (TEM00) modes, except for a little complicating factor in the round-trip by pass on the surface of the aperture mirror. The results showed that the diffraction loss procedure is just the continuate for the earlier work, except that the field intensities change for TEM01, as that of TEM00, as such, it has a direct effect on the equation fitting it. The Combination of experimental and Theoretical results in this study are in excellent agreement as in g = 0.80 and they were both functions of the physical parameters of the active medium and the laser resonator. References AKSENOV, V. P., KOLOSOV, V. V., POGUTSA, C. E. & FILIMONOV, G. A. Dependence of the density of the probability of turbulent fluctuations of the orbital angular moment of a laser beam on the size of the receiver aperture. 26th International Symposium on Atmospheric and Ocean Optics, Atmospheric Physics, 2020. International Society for Optics and Photonics, 1156029. AST, S., DI PACE, S., MILLO, J., PICHOT, M., TURCONI, M., CHRISTENSEN, N. & CHAIBI, W. 2021. Higher-order Hermite-Gauss modes for gravitational waves detection. Physical Review D, 103, 042008. BARRIGA, P., BHAWAL, B., JU, L. & BLAIR, D. G. 2007. Numerical calculations of diffraction losses in advanced interferometric gravitational wave detectors. JOSA A, 24, 1731-1741. BHAWAL, B. 2005. Diffraction losses of various modes in advanced LIGO arm cavity. LIGO Tech. Note, LIGOT050234-00-E (LIGO, 2005). BISTI, F., ALEXEEV, I., LANZETTA, M. & SCHMIDT, M. 2021. A simple laser beam characterization apparatus based on imaging. Journal of applied research and technology, 19, 98-116. BORNEIS, S., LAŠTOVIČKA, T., SOKOL, M., JEONG, T.-M., CONDAMINE, F., RENNER, O., TIKHONCHUK, V., BOHLIN, H., FAJSTAVR, A. & HERNANDEZ, J.-C. 2021. Design, installation and commissioning of the ELI-Beamlines high-power, high-repetition rate HAPLS laser beam transport system to P3. High Power Laser Science and Engineering, 9. COLDREN, L. A. 2021. Review of key vertical-cavity laser and modulator advances enabled by advanced MBE technology. Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films, 39, 010801. FALCÓN, R. E.-C., ESCUELA, A. M., SENDRA, J. S. & SANTANA, D. F. 2019. Subsampling techniques for gaussian laser beam radius estimation using a configurable quadrant photodiode (CQD). Optics & Laser Technology, 109, 412-417. GEORGE, A., WEBER, H. J. & HARRIS, F. 2013. Mathematical Methods for Physicists. A Comprehensive Guide. Academic Press, Elsevier. HASHEMIAN, S. & AKOU, H. 2020. Hollow high-quality electron beam generation by cyclotron autoresonance in laser-induced acceleration. Optik, 202, 163708. HU, X.-Q., LEI, X.-C., SALSAC, A.-V. & BARTHÈS-BIESEL, D. 2020. Minuet motion of a pair of capsules interacting in simple shear flow. Journal of Fluid Mechanics, 892. KARBSTEIN, F. 2018. Vacuum birefringence in the head-on collision of x-ray free-electron laser and optical high-intensity laser pulses. Physical Review D, 98, 056010. KOGELNIK, H. & LI, T. 1966. Laser beams and resonators. Applied optics, 5, 1550-1567. LAKHOTIA, H., KIM, H., ZHAN, M., HU, S., MENG, S. & GOULIELMAKIS, E. 2020. Laser picoscopy of valence electrons in solids. Nature, 583, 55-59. LI, T. 1965. Diffraction loss and selection of modes in maser resonators with circular mirrors. The Bell System Technical Journal, 44, 917-932. SASNETT, M. 2020. Propagation of multimode laser beams–the M2 factor. The physics and technology of laser resonators. CRC Press. SIEGMAN, A. E. 1986. Lasers. Mill Valley, CA: Univ. Science, 298-301. SOHN, I.-B., CHOI, H.-K., NOH, Y.-C., KIM, J. & AHSAN, M. S. 2019. Laser assisted fabrication of micro-lens array and characterization of their beam shaping property. Applied Surface Science, 479, 375-385. SVELTO, O. & HANNA, D. C. 1998. Principles of lasers, Springer. URUNKAR, T., PATIL, S., VALKUNDE, A., VHANMORE, B., GAVADE, K. & TAKALE, M. 2018. Effect of Critical Beam Radius on Self-focusing of cosh-Gaussian Laser Beams in Collisionless Magnetized Plasma. Communications in Theoretical Physics, 70, 220. VERDEYEN, J. T. 1995. Laser Electronics, 1995. Prentice Hall, Inc. WANG, M., MA, Y., SHENG, Q., HE, X., LIU, J., SHI, W., YAO, J. & OMATSU, T. 2021. Laguerre-Gaussian beam generation via enhanced intracavity spherical aberration. Optics Express, 29, 27783-27790. ZHOU, G., JI, Z. & RU, G. 2018. Complete Analytical Expression of Lorentz-Hermite-Gauss Laser Beams. Lasers in Engineering (Old City Publishing), 40. ZHU, M., XU, N., ROSHANZADEH, B., BOYD, S., RUDOLPH, W., CHAI, Y. & SHAO, J. 2020. Nanolaminate-based design for UV laser mirror coatings. Light: Science & Applications, 9, 1-6. ZHU, X., WU, D., WANG, Y., YU, F., LI, Q., QI, Y., KNIGHT, J., CHEN, S. & HU, L. 2021. Delivery of CW laser power up to 300 watts at 1080 nm by an uncooled low-loss anti-resonant hollow-core fiber. Optics Express, 29, 1492-1501.